Une apostrophe végétale : la mandragore d’Alfred Jarry - Bolte, Rike (Studia Romanica Posnaniensia, 2025)
What about ‘Pataphysics in the 21st century – Alfred Jarry’s philosophical and scientific concept, governed by the rules of the absurd, the principle of discovery and the derogation of rules? An excursion into the world of plants will provide an answer to this question, and a recourse to ‘Pataphysics may be useful for the explorations of the human-plant relationship. Indeed, Jarry’s work offers an eco-subliminal reading. The subject of the following article is one of Jarry’s most challenging works, namely the collection of prose and versified pieces Les Minutes de sable mémorial (1894), classified as a sketch of the principles of Ubu (a figure which, as we know, is composed in part of plants). Starting from post- and hypermodern perspectives on ‘Pataphysics – those of Baudrillard and the writing duo Deleuze and Guattari – the article examines the entry of the plant world into ‘Pataphysics and then focuses a paradigm of the human-plant relationship: the mandrake. This excursion into the mythologically charged terrain (or earth, soil) of the mandrake concludes with a close reading of certain patabotanical aspects, among which the rhizomatic (anthropomorphized) figure plays a central role.